Attributes for Staging Successful Wine Festivals - Taylor, Ruth; Shanka, Tekle (Cognizant Communication Corporation, 2002)
With the increase in special interest tourism, there is a niche for investigating tourism potential within the rural and urban peripheral zone. Wine-producing regions located in the urban–rural peripheral zone not only provide the spatial context for the development of wine tourism, but with the inclusion of a temporal ele ment, can also provide the context for the staging of wine-related festivals and events. This article provides a unique analysis of the visitor market to a wine festival staged in an urban–rural peripheral zone. It investi gates the factors contributing to the successful staging of such an event and demonstrates the importance of both the location factor and facilities factor contributing to the overall success of the event. This research highlights the factor of location and its composite variables as being of primary importance for event man agers when staging wine festivals in urban–rural peripheral regions.